2024
DOI: 10.1063/5.0177658
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of wire spark erosion machining of Grade 9 titanium alloy (Grade 9) using a hybrid learning algorithm

Manikandan Natarajan,
Thejasree Pasupuleti,
Jayant Giri
et al.

Abstract: Manufacturing has grown challenging because of the increased usage of harder materials, such as titanium alloys, in many industries, such as aerospace, automobiles, and marine. Conventional material removal procedures are not suitable for these tough materials due to their increased hardness and slow machinability. Wire Electrical discharge machining (WEDM) is a modern approach for material removal, particularly for harder materials, such as titanium alloys, nickel alloys, hard particle reinforced metal matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…While variance analysis was employed mainly to find the contribution of parameters, coupled methods were used to predict the optimal values of inputs. [15][16][17][18][19][20][21][22] Research on HAM of various ferrous and non-ferrous materials is observed from an exhaustive literature survey. However, a very limited analysis is available in the study of striation features and cut surface characteristics in the fabrication of the MMC Al6061/Al 2 O 3 /B 4 C using the HAM process.…”
Section: Article Pubsaiporg/aip/advmentioning
confidence: 99%
“…While variance analysis was employed mainly to find the contribution of parameters, coupled methods were used to predict the optimal values of inputs. [15][16][17][18][19][20][21][22] Research on HAM of various ferrous and non-ferrous materials is observed from an exhaustive literature survey. However, a very limited analysis is available in the study of striation features and cut surface characteristics in the fabrication of the MMC Al6061/Al 2 O 3 /B 4 C using the HAM process.…”
Section: Article Pubsaiporg/aip/advmentioning
confidence: 99%